IMPLEMENTASI METODE LATIHAN UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM MENYUSUN EVALUASI PEMBELAJARAN DI SEKOLAH LUAR BIASA NEGERI SIAK KABUPATEN SIAK - Maidar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article is based on research on teachers’ low ability in designing learning evaluations at the Public Special School in Siak. The type of research is School Action Research (PTS), which was located at the Siak Public Special School and was designed for the teachers. The main reason came from the observation results and information from teachers in which the teachers’ ability in designing learning evaluations was still categorized as relatively lacking. This School Action Research was conducted at the Siak Public Special School. The population involved 19 teachers at the Siak Public Special School and all of them were a sample. The study consisted of two cycles, which were implemented in two meetings. Based on the description of data processing and discussion, it was obtained that the teacher's ability in evaluating was achieved at 61.6 in cycle I with the high category and it was increased to 75.3 in cycle II with the high category. It means that the implementation of the training method activities to improve teacher evaluation ability at the Siak Public Special School was said successful to be implemented.